Fatores da satisfação, fidelidade e recomendação em serviço de saúde: estudo em setor ambulatorial de hospital - Silva, Arivalda Bezerra da (2009)
This thesis deals with the factors affecting customer satisfaction, loyalty and recommendation in the health care sector. It is adapted a model proposed by Johnson et al. (2001) of quality and loyalty antecedent factors and it is conducted a survey with a sample of 109 customers of a hospital on the ambulatory in Natal city, a capital of a Northeastern State of Brazil. It is carried descriptive and multiple regression statistical analysis. The main findings related to satisfaction are that quality factors of doctor professionalism, clerical staff efficiency, consultancy room comfort, time to provide the medical consultancy but also hospital localization are the most significant factors affecting satisfaction. Regarding personal full loyalty, satisfaction with the hospital and affective commitment are the main factors yet for partial loyalty image and calculate commitment play the main role. For recommendation satisfaction, image and brand are the main factors. The overall model used fairly explains the satisfaction, loyalty and recommendation outcomes with varying factors regarding each final purpose, e.g. loyalty or recommendation